Dispute Resolution Through Local Institutional Mechanisms in the Baduy Indigenous People and Their Relevance to National Legal Pluralism - Muhammad Tahsin Roy; Iwan Darmawan; Mahipal Mahipal (Civiliza Publishing, 2026)
This study aims to analyze the dispute resolution mechanism through local institutions in the Baduy indigenous people and its relevance to national legal pluralism in Indonesia. On the one hand, the Baduy customary mechanism based on the philosophy of pikukuh and the concept of mutual forgiveness has proven to be effective in resolving conflicts quickly, participatoryly, and oriented towards restoring social-spiritual harmony at no cost. However, on the other hand, its implementation faces structural and normative challenges when interacting with the formal justice system, such as the lack of documentation of decisions, the lack of standardized due process, and the potential for overlapping jurisdictions. This study uses a normative-empirical legal approach with a qualitative case study method, through the analysis of regulatory documents, literature reviews, and in-depth interviews with key sources. The results of the study show that the local institutions of Baduy are in substantive harmony with the principles of restorative justice and preventive legal protection, but their constitutional recognition is still partial at the field level. This study recommends a complementary harmonization model that includes: (1) declarative registration of customary decisions as a peace deed in the District Court, (2) the preparation of institutional collaboration protocols (MoU/Joint Decree), (3) joint training on the principles of restorative justice and human rights, and (4) continuous legal assistance. Thus, the coexistence of customary law and national law can be realized in a healthy manner without sacrificing cultural autonomy and guarantees of human rights protection.